Speeding stroke recovery? A systematic review of amphetamine after stroke - Sprigg, Nikola; Bath, Philip M.W. (Elsevier, 2009)
Introduction: The use of drugs to enhance recovery (“rehabilitation pharmacology”) has been assessed. Amphetamine can improve outcome in experimental models of stroke, and several small clinical trials have assessed its use in stroke. Methods: Electronic searches were performed to identify randomised controlled trials of amphetamine in stroke (ischaemic or haemorrhagic). Outcomes included functional outcome (assessed as combined death or disability/dependency), safety (death) and haemodynamic measures. Data were analysed as dichotomous or continuous outcomes, using odds ratios (OR), weighted or standardised mean difference, (WMD or SMD) using random-effects models with 95% confidence intervals (95% CI); statistical heterogeneity was assessed. Results: Eleven completed trials (n=329) were identified. Treatment with amphetamine was associated with non-significant trends to increased death (OR 2.78 (95% CI, 0.75– 10.23), n=329, 11 trials) and improved motor scores (WMD 3.28 (95% CI −0.48–7.04) n=257, 9 trials) but had no effect on the combined outcome of death and dependency (OR 1.15 (95% CI 0.65–2.06, n=206, 5 trials). Amphetamine increased systolic blood pressure (WMD 9.3 mmHg, 95% CI 3.3–15.3, n=106, 3 trials) and heart rate (WMD 7.6 beats per minute (bpm), 95% CI 1.8–13.4, n=106, 3 trials). Despite variations in treatment regimes, outcomes and follow-up duration there was no evidence of significant heterogeneity or publication bias. Conclusion: No evidence exists at present to support the use of amphetamine after stroke. Despite a trend to improved motor function, doubts remain over